Penerapan JavaScript React pada perancangan front-end website UMKM Jemari Ragil - Elsie Naresvari; Susetyo, Yeremia Alfa (Fakultas Teknologi Informasi, Universitas Kristen Satya Wacana, 2025)
UMKM Jemari Ragil has successfully digitized its business by joining the e-commerce platform Shopee since September 2023 and reached international markets such as Malaysia. Although marketing strategies through Instagram, WhatsApp, and TikTok are effective, challenges arise from the limited understanding of technology by customers, who often need guidance in using E-commerce. This research aims to implement React JavaScript for the Jemari Ragil' MSME website. The goal is to overcome the main obstacles faced by the owner of Jemari Ragil. The research method includes problem and needs analysis, design and system design, implementation or application development, and system testing. The result of this research is the successful implementation of JavaScript React to build an efficient and interactive MSME website interface. Through the results of Usability Testing system testing and measured using the System Usability Scale (SUS) which resulted in a score of 76 with a good category, indicating that the system can be accepted by users and meets the established usability standards.